2019
DOI: 10.1093/nutrit/nuz029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary intervention, with or without co-interventions, on inflammatory markers in patients with nonalcoholic fatty liver disease: a systematic literature review

Abstract: Context Nonalcoholic fatty liver disease (NAFLD) represents a spectrum of liver disorders, ranging from simple steatosis to nonalcoholic steatohepatitis (NASH), with inflammation acting as a key driver in its pathogenesis and progression. Diet has the potential to mediate the release of inflammatory markers; however, little is known about the effects of various diets. Objective This systematic review aimed to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…An overall decrease in C-reactive protein, TNF-α and IL-6 and an increase in adiponectin levels, indicated an improvement in the inflammatory and possibly the oxidative status of NAFLD patients [61]. The authors suggest chronic inflammatory response in NAFLD/NASH as a putative therapeutic target area, and also propose inflammatory cytokines and adipokines as noninvasive markers of disease [61]. This is supported by previous studies showing a correlation between disease activity and serum TNF-α and adiponectin levels in children and adult biopsy-proven NAFLD patients warranting inflammation and oxidative stress as viable therapeutic targets of NASH [62][63][64].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An overall decrease in C-reactive protein, TNF-α and IL-6 and an increase in adiponectin levels, indicated an improvement in the inflammatory and possibly the oxidative status of NAFLD patients [61]. The authors suggest chronic inflammatory response in NAFLD/NASH as a putative therapeutic target area, and also propose inflammatory cytokines and adipokines as noninvasive markers of disease [61]. This is supported by previous studies showing a correlation between disease activity and serum TNF-α and adiponectin levels in children and adult biopsy-proven NAFLD patients warranting inflammation and oxidative stress as viable therapeutic targets of NASH [62][63][64].…”
Section: Discussionmentioning
confidence: 96%
“…In accordance, the introduction of a diet intervention in the present study resulted in a reduction in dyslipidemia, hepatic lipid accumulation and liver weight. A recent systematic literature review found that low-calorie diets improve the inflammatory profile in patients diagnosed with NAFLD [61]. An overall decrease in C-reactive protein, TNF-α and IL-6 and an increase in adiponectin levels, indicated an improvement in the inflammatory and possibly the oxidative status of NAFLD patients [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a healthy lifestyle has been proposed as the cornerstone for disease management (8). Furthermore, dietary interventions aiming to improve the inflammatory profile have proven beneficial in patients with NAFLD (9). There is also growing scientific interest in a variety of supplements and herbal products, as potential therapeutic and/or preventive approaches for NAFLD (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is characterized by lipid accumulation in the liver (hepatic steatosis) in the absence of alcohol consumption and increased circulating levels of the hepatic enzyme alanine aminotransferase (ALT). Hepatic steatosis has been associated with components of the metabolic syndrome (abdominal obesity, insulin resistance, hypertriglyceridemia) [7] and low grade systemic chronic inflammation [8], all factors known to predispose to the development of atherosclerosis in the vessel wall.…”
Section: Introductionmentioning
confidence: 99%